The Total Factor Productivity in Strategic Food Crops Industry of Malaysia - Othman, Kamarudin; Baharuddin, Amir Hussin (Asian Journal of Agriculture and Rural Development, 2015)
Total Factor Productivity (TFP) may indicate the long-term economic growth of a country. In addition, it is also a comprehensive measure of the level of productivity in the economy. Therefore, these study attempts to investigate the TFP for Malaysia paddy sub-sector. The study was conducted in four Muda Agricultural Development Authorities (MADA) regions and employed a seasonal the series of data from 1996 to 2011. Result has found that the actual TFP growth is below than 5 percent for each season. The study also found that the actual TFP trend has been volatile over time. Study has further investigated the factors affecting TFP growth in the Malaysian paddy industry for the entire period. Seven selected factors are found to be associated with striking TFP growth. The result has discovered that all the selected factors are important in influencing the paddy production in Malaysia. However, the magnitude is different for each region.